HASIL BELAJAR SISTEM TATA SURYA PENERAPAN DEMONSTRASI MENGGUNAKAN MEDIA AUDIO-VISUAL SISWA KELAS VI SDN 025/XI DESA GEDANG - Ondriadi Ondriadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
his study originated from lack of enthusiasm following learning, less satisfactory learning outcomes, most students get grades below the minimum learning mastery standard. This study aims To improve learning outcomes about the solar system in grade 6 students SDN 025 / XI Gedang Village through the implementation of demonstration methods using audio visual media. Subjects in this study were students of grade 6 SDN 025 / XI Desa Gedang with the material of Solar System. The implementation of the improvement consists of two cycles where each cycle is held twice. Place of Action Class Action research that is at SDN 025 / XI Gedang Village Sungai Penuh Full River City. In each cycle is divided into four stages, namely: Planning, Implementation of action, Observation and Evaluation, and Reflection. The data required in this study were obtained through observation of learning processing by demonstration method, observation of student and teacher activity, and formative test. The result of class action research using two cycle pattern, it can test the hypothesis of action proposed in this research. The result shows that in cycle II the classical has reached the completeness of the expected learning result, because the student who get the value of ≥ 70 is only 90% bigger than the percentage of desired completeness that is equal to 85%. The use of demonstration methods and audio visual media tailored to the teaching materials can help students to more easily understand the learning materials presented in appeal using only the lecture method only